(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
أثبتت نتائج التحليل الهيدروكيميائي التي أجريتها على عينات من ثلاثين بئرا مسبورا″في تشكيلة النيوجين الحاملة للمياه في إحدى المناطق الجافة حقيقة العلاقة الطردية بين ازدياد ملوحة المياه وازدياد الناقلية الكهربائية لها. بالإضافة للتوصل إلى التناسب الطردي بين انخفاض المنسوب الهيدروستاتيكي لمياه الآبار, نتيجة الضخ الجائر , و ازدياد ملوحة مياهها نتيجة رفد الحامل المائي بمياه الصرف الزراعي, والاستنتاج ينذر بالخطر الحقيقي على احتياطي المياه الجوفية كما″ ونوعا″, والتوصية هي العمل على إيجاد الحلول الجادة للحد من هذه الظاهرة والمتمثلة بوقف استنزاف المياه من الآبار بالتزامن مع البحث عن مصادر مياه بديلة. This research has been conducted on thirty wells. The major finding is the fact of direct proportionality between increasing of water salinity and increasing of electrical conductivity. Furthermore, there is a direct proportionality between decreasing of water level in wells because of extreme pumping and increasing of water salinity because of agriculture drainage. Therefore, the research highlights the real danger on underground water reserve quantitatively and qualitatively. The situation requires serious solutions to limit this phenomenon. One of these accepted solutions is to stop water exhaustion from wells in addition to executing research for having substitute water sources.